2019
DOI: 10.1001/jamainternmed.2018.5100
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Trauma of Hospitalization With 30-Day Readmission or Emergency Department Visit

Abstract: IMPORTANCE Trauma of hospitalization refers to the depersonalizing and stressful experience of a hospital admission and is hypothesized to increase the risk of readmission after discharge. OBJECTIVES To characterize the trauma of hospitalization by measuring patient-reported disturbances in sleep, mobility, nutrition, and mood among medical inpatients, and to examine the association between these disturbances and the risk of unplanned return to hospital after discharge. DESIGN, SETTING, AND PARTICIPANTS This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
1
31
2
Order By: Relevance
“…Delayed discharges have many negative impacts on patient safety, quality of care as well as health system utilization and costs. First, prolonged hospitalization increases risk for adverse outcomes including accelerated functional decline, delirium, pressure ulcers, nosocomial infections and falls [812]. Second, delayed discharge creates patient safety challenges by contributing to hospital overcrowding and reduced accessibility to finite acute care resources.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed discharges have many negative impacts on patient safety, quality of care as well as health system utilization and costs. First, prolonged hospitalization increases risk for adverse outcomes including accelerated functional decline, delirium, pressure ulcers, nosocomial infections and falls [812]. Second, delayed discharge creates patient safety challenges by contributing to hospital overcrowding and reduced accessibility to finite acute care resources.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, while we captured in-hospital complications, our dataset did not include other events in the hospital (eg, delirium, inadequate nutrition and prolonged immobility) that are more difficult to quantify but may also contribute to readmission risk. 3 4 30 Notably, a recent study by Rawal et al 30 of 207 medical inpatients found that those reporting disturbances in multiple domains of sleep, mobility, nutrition and mood were significantly more likely to be readmitted within 30 days than those reporting little or no disturbance, even after adjustment for age, sex, comorbidity burden, laboratory abnormalities and length of stay. To our knowledge, similar data have not been published for 180-day readmission, and further study is therefore needed to evaluate whether the hospital environment affects outcomes within this timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…Division of General Internal Medicine, Toronto Western Hospital, University Health Network, Toronto, Ontario, Canada; 2 Division of General Internal Medicine, Department of Medicine, University of Toronto, Toronto, Ontario, Canada; 3 HoPingKong Centre for Excellence in Education and Practice, University Health Network, Toronto, Ontario, Canada; 4 Department of Pharmacy, Toronto Western Hospital, University Health Network, Toronto, Ontario, Canada; 5 Division of General Internal Medicine, Toronto General Hospital, University Health Network, Toronto, Ontario, Canada.…”
mentioning
confidence: 99%